2022
DOI: 10.1007/s10840-022-01148-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of standard bipolar amplitude voltage thresholds to identify late potential channels in ventricular tachycardia ablation

Abstract: Background Ventricular tachycardia (VT) is caused by the presence of a slow conduction channel (CC) of border zone (BZ) tissue inside the scar-core tissue. Electroanatomic mapping can depict this tissue by voltage mapping. Areas of slow conduction can be detected as late potentials (LPs) and their abolition is the most accepted ablation endpoint. In the current guidelines, bipolar voltage thresholds for BZ and core scar are 1.5 and 0.5 mV respectively. The performance of these values is controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Of note, VNS protocol was different with Vaseghi et al performing pulsed VNS (15 s on, 15 s off) as compared to steady-state VNS protocol used in this study. Interestingly in that study, scar borders were defined with conventional bipolar voltages of 0.5–1.5 mV and scars being 0.05–0.5 mV although MRI revealed areas of normal myocardium recording <0.5 mV, supporting the notion of variable (often lower) bipolar voltages in border zones [ 18 ]. This may confound the regional electrophysiologic effects of VNS observed in the border zones defined by conventional bipolar voltage definition.…”
Section: Discussionmentioning
confidence: 83%
“…Of note, VNS protocol was different with Vaseghi et al performing pulsed VNS (15 s on, 15 s off) as compared to steady-state VNS protocol used in this study. Interestingly in that study, scar borders were defined with conventional bipolar voltages of 0.5–1.5 mV and scars being 0.05–0.5 mV although MRI revealed areas of normal myocardium recording <0.5 mV, supporting the notion of variable (often lower) bipolar voltages in border zones [ 18 ]. This may confound the regional electrophysiologic effects of VNS observed in the border zones defined by conventional bipolar voltage definition.…”
Section: Discussionmentioning
confidence: 83%
“…29 EAM with a bipolar voltage cut off <1.5 mV showed a good correlation with transmural scar but not with non-transmural heterogenous scar. 29,34 Histological studies have also shown that EAM (bipolar and unipolar) did not demonstrate a good correlation when identifying fibrosis in patients with NICM. 35 The importance of scar location was highlighted in another study, which showed just a 2 mm rim of viable endocardium overlying otherwise transmural scarring could result in a falsely normal bipolar voltage map, although a unipolar map can sometimes overcome this limitation.…”
Section: Contrast-enhanced Magnetic Resonance Imagingmentioning
confidence: 99%
“…However, these thresholds cut-offs were found mainly in studies of patients with ischemic heart disease and have not been well validated in patients with NICM. In a cross-sectional study, Roca-Luque et al examined the performance of conventional voltage thresholds and found only moderate diagnostic yield in identification of scars and delineation of border zone tissue, with worse performance in patients with NICM [2], In ICM pts, they found mean voltages that better identified the conduction channels in core tissue and border zone were 0.32 (0.02-2 mV) and 1.84 (0.3-6 mV). These values did not differ significantly between ICM and NICM pts (p = 0.09).…”
Section: Mapping Techniques For Treatment Of Ventricular Arrhythmiasmentioning
confidence: 99%